BENTUK, FUNGSI, DAN MAKNA MONUMEN TUANKU IMAM BONJOL KABUPATEN PASAMAN - YOAN WAHYUDI, Ir. Drs. Heldi, M.Si. Ph.D., Drs. Efrizal, M.Pd. (Serupa The Journal of Art Education, 2016)
This research is done because there are still societies who do not understand the form, purpose, and meaning of the Tuanku Imam Bonjol Monument. The purpose of this research are (1) describing the form, (2) knowing the purpose, and (3) comprehend the meaning of the Tuanku Imam Bonjol monument in Pasaman. The primary source of this research is orally information given by the informant. This is a descriptive quantitative research. The findings of this research is the form of Tuanku Imam Bonjol monument which consist of the foundation, postek, and figure of the monument. The purpose of the Tuanku Imam Bonjol monument is as the representative of the people of Pasaman. The monument of Tuanku Imam Bonjol shows the meaning of heroic effort of a leader who stands based on the islamic norms at Minang Kabau.Kata kunci: bentuk, fungsi, dan makna monumen Tuanku Imam onjol